One-Man Lobby in America: Vahan Cardashian (1883-1934) - Kürşad; Karacagil (Gazi Akademik Bakış)
Turco-American relationship had a long history with cordial relations. Diplomatic relations that were severed in 1917 with the entrance of US into the World War could be reestablished only in 1927. One of the major factors in this delay was the anti-Turkish activities undertaken by Armenians living in US. The figure of Vahan Cardashian (Kardaşyan) who functioned almost as a one-man lobby against Turkey until 1934 is especially worthy of attention. Born in Kayseri in 1883, Cardashian completed his higher education in the same town and received a Law degree at Yale University. He nurtured good relations with Ottoman officials until 1915 and even served as translator in the Empire’s Consulate in New York. After 1915, however, Cardashian started his anti-Turkish activities. Among these activities were the foundation of an independent Armenia, one of the issues discussed in the Sevrès Treaty, non-ratification of the Turco-American treaty signed on 6 August 1923 in Lausanne and his negative propaganda against Turkish ambassador to Washington, Ahmed Muhtar Bey.